An Elucidation on the Stakeholder Concept in Organizational Studies - Louie Giray (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2022)
The aim of this manuscript is to shed light on the stakeholder concept. Particularly, it strives to define and classify the concept of stakeholders. This is done because many are still confused with this concept and misuse the term in various occasions. Without having this knowledge, organizational leaders may lead the disarray in meetings and planning. Consequentially, this lack of knowledge base of leader can drive toward the ineffectiveness. In this paper, the definition of stakeholder is also highlighted and explained through the words of experts in organizational studies. Examples are given to further concretize the meaning of stakeholder. Different typologies of stakeholders are discussed, together with roles and possible difficulties. It is anticipated that misperception regarding this topic will be reduced or better eliminated. Moreover, this article accentuates on the inevitable interaction between stakeholders and an organization, which determines an organization's sustainable and survival rates. It is emphasized that an organization will degrade in its posture and effectiveness if it runs on its own, without paying much attention to its stakeholders.